Assessment of quality of care for hospitalized non-COVID-19 older adult patients with pneumonia before and after the COVID-19 pandemic - HeeKyoung Choi; Young Keun Kim; BumSik Chin; So Youn Shin; Sun Bean Kim; Euna Han (Elsevier, 2024)
Background: There is limited research into the clinical implications of the coronavirus disease 2019 (COVID-19) pandemic for non-COVID-19 pneumonia in older adults, as well as their quality of care or outcomes. This study aims to assess the process and outcome quality of care for hospitalized older adult patients with pneumonia before and after the pandemic. Methods: A retrospective cohort of older adult patients (age ≥ 65) hospitalized for non-COVID pneumonia were recruited from five Korean hospitals (January 20, 2019, to January 19, 2021). The quality of care before and after the COVID-19 pandemic was evaluated. Results: A total of 7356 hospitalization episodes of older adult pneumonia were identified, and 978 cases (552 pre-pandemic and 426 during the pandemic) were analyzed. The pneumonia severity score was higher during the pandemic, and the waiting time from the emergency room to admission was also longer. Furthermore, the pneumonia mortality rate during the pandemic was higher than that in the pre-pandemic period (in-hospital mortality: 10.1% vs. 18.1%; 90-day mortality: 11.6% vs. 22.3%). A significantly higher mortality risk was observed during the pandemic than in the period prior (adjusted odds ratio: 1.74, 95% confidence interval: 1.14-2.63). Conclusions: While the quality of care for hospitalized pneumonia has been maintained during the pandemic, there has been an increase in mortality rates. Further investigations are needed to understand the underlying causes of this increase.